EBV induced Evans syndrome in a patient of SLE related MAS - WeiBin Li; Yini Chen; Ya Chen; Meng Zhao; Shenghang Zhang (Medicine, 2026)
Rationale: Epstein-Barr virus (EBV) induced Evans syndrome in systemic lupus erythematosus (SLE) related macrophage activation syndrome (MAS) is rare with the incidence rate of 0.9% to 9% and the mortality rate of about 4% to 19%, which are misdiagnosed as hemophagocytic lymphohistiocytosis. Patient concerns: A 15-years old female was admitted due to abdominal pain and fever. Physical examination showed butterfly-shaped erythema on her face and scattered lymph nodes of bilateral neck with a diameter of 1.5 cm × 1.0 cm. Pharyngeal mucosal congestion, bilateral tonsil swelling, and palpable 1 cm below the liver rib and no palpable spleen were observed. Medical history revealed recurrent facial erythema after puberty, which is aggravated by exposure to sunlight. Diagnoses: Based on the results of complete blood cell count, biochemical and immunologic examination and bone marrow cytology, EBV-induced Evans syndrome of SLE-related MAS was reached. Interventions: Ceftriaxone, oseltamivir, methylprednisolone, omeprazole, cyclosporine, and high-dose immunoglobulin were administrated and after 20 days the patient was discharged and regularly followed up. Outcomes: After 20 days of administration, the patient was significantly improved and discharged. Lessons: Disease history, laboratory tests, and differential diagnosis contribute to the confirmation of EBV-induced Evans syndrome in SLE-related MAS.